Mobilizing Global Knowledge Refugee Research in an Age of Displacement - McGrath, Susan; Young, Julie E.E (University of Calgary Press, 2019)
An examination of, and guide to, the challenges and responsibilities of doing research with displaced peoples while respecting their complex needs. In 2018, the United Nations High Commission for Refugees documented a record high 71.4 million displaced people around the world. As states struggle with the costs of providing protection to so many people and popular conceptions of refugees have become increasingly politicized and sensationalized, researchers have come together to form regional and global networks dedicated to working with displaced people to learn how to respond to their needs ethically, compassionately, and for the best interests of the global community. Mobilizing Global Knowledge brings together academics and practitioners to reflect on a global collaborative refugee research network. Together, the members of this network have had a wide-ranging impact on research and policy, working to bridge silos, sectors, and regions. They have addressed power and politics in refugee research, engaged across tensions between the Global North and Global South, and worked deeply with questions of practice, methodology, and ethics in refugee research. Bridging scholarship on network building for knowledge production and scholarship on research with and about refugees, Mobilizing Global Knowledge brings together a vibrant collection of topics and perspectives. It addresses ethical methods in research practice, the possibilities of social media for data collection and information dissemination, environmental displacement, transitional justice, and more. This is essential reading for anyone interested in how to create and share knowledge to the benefit of the millions of people around the world who have been forced to flee their homes.